2013
DOI: 10.1161/hypertensionaha.111.00026
|View full text |Cite
|
Sign up to set email alerts
|

Does Dairy Food Intake Predict Arterial Stiffness and Blood Pressure in Men?

Abstract: Hypertension (DASH) trial, which revealed that a diet high in fruit and vegetables and low-fat dairy products (3 servings per day) was associated with lower systolic (SBP; 11-12 mm Hg) and diastolic blood pressure (DBP; 6-7 mm Hg). A recent systematic review by Ralston et al 7 summarized the evidence from 5 cohort studies investigating relationships between consumption of milk and dairy products and SBP/DBP or hypertension and concluded that consumption of these foods is likely to benefit blood pressure regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…Pulse wave velocity measures the speed of propagation of the pressure wave front along the artery, whereas the augmentation index is calculated from the blood pressure wave form and is based on the degree of wave reflection. Significant associations between dairy product intake and arterial pulse wave velocity have been shown in cross-sectional (136) and longitudinal (126) cohort studies. Livingstone et al (126) presented data from the Caerphilly Prospective Study, based on 2512 men followed up for a mean of 28 years and showed a significant inverse relationship between dairy product intake and augmentation index.…”
Section: Dairy Proteins and Blood Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulse wave velocity measures the speed of propagation of the pressure wave front along the artery, whereas the augmentation index is calculated from the blood pressure wave form and is based on the degree of wave reflection. Significant associations between dairy product intake and arterial pulse wave velocity have been shown in cross-sectional (136) and longitudinal (126) cohort studies. Livingstone et al (126) presented data from the Caerphilly Prospective Study, based on 2512 men followed up for a mean of 28 years and showed a significant inverse relationship between dairy product intake and augmentation index.…”
Section: Dairy Proteins and Blood Lipidsmentioning
confidence: 99%
“…In addition, the magnitude of blood pressure reduction was of greater magnitude after the diet rich in low-fat dairy products compared with the fruit and vegetable-rich diet, which omitted dairy products altogether (119) . The findings from cross-sectional and prospective observational studies have shown an inverse association between consumption of dairy products, particularly low-fat varieties, and risk of hypertension (64,65,(120)(121)(122)(123)(124)(125)(126) . The recent results from the Framingham Heart Study Offspring Cohort (n 2636) also showed benefit from low/reduced fat dairy products (127) .…”
Section: Dairy Proteins and Blood Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the East Finland cohort was located in Karelia (Keys et al 1958), then an isolated and icebound region for most of the year while the West Finland cohort was centred near Turku and included a substantial proportion of Swedes (Karvonen et al 1970). During winter the rations were reduced to milk and other dairy products, bread, and potatoes with small amounts of other foodstuffs (Roine et al 1958), hardly well balanced but hardly a death sentence, given the benefits of dairy product consumption for CVD and the metabolic syndrome (Evans et al 1995;Elwood et al 2010;Livingstone et al 2013). Indeed, there was little difference between East and West Finland in their diets, apart from a small increase in diversity in the West, and reduced vitamin C, vitamin E, and iodine in the East.…”
Section: The Epidemiology Of Cardiovascular Disease and Saturated Fatmentioning
confidence: 99%
“…An increase in cfPWV by 1 m/s corresponds to an adjusted risk increase of 14, 15 and 15 % in total cardiovascular events, cardiovascular mortality and all-cause mortality, respectively (66) . Using this gold standard measure, dairy food intake has been shown to have a favourable effect on arterial stiffness, as well as overall cardiovascular profile and reduced mortality (68)(69)(70)(71) . However, the evidence regarding the effect of Ca in the form of supplements on arterial stiffness is less consistent.…”
Section: Discussionmentioning
confidence: 99%